Chemotherapy: abstract Agustín D’Auria - Chacón, Reinaldo D (Cirugía del Uruguay, 2021)
100 soft tissue sarcomas were studied (60 men and 40 women), corresponding to the Hospital de Clínicas and Oncology Institute of Montevideo.